Optimisation of The Value in-use of The Refractory Submerged Entry Nozzle: Implication of preheating failures - EBRIMA SALLAH (2023)
There is a need to understand the preheating process implication on the performance of a submerged entry nozzle (SEN) that allows the transfer of liquid steel from tundish to mould. The SEN suffers from failure attributed to improper preheating, leading to sudden thermal shock failures and oxidation of its carbonaceous matrix weakening its resistance to fracture. Process knowledge concerning temperature and time period that the SEN is exposed is often lacking/or insufficient in sponsor site (steel user of product). It is not currently being practised or possible to monitor the temperature of the SEN during its use. This is perhaps due to lack of cost-effective methods for sponsor, which therefore necessitates a new approach in obtaining quantitative and effect profiling methods that can address the gap in process knowledge implications on SEN performance. In future the same profiling methods are suggested is a way to generate datasets for modelling and predicting the missing process variables that impact on performance (i.e., the effect of time and temperature combined) since the material displays distinguishable profiles based on preheat treatment. The data can be further processed to address failure classification. Three of the same supplier batch SENs were characterised in this study, comprising of one virgin SEN and two industrially as-received preheated SENs (i.e., one heated for three hours and the other for six hours). Carbon phases present within the SEN were used as a marker when profiling and assess oxidation resistance. The synergistic use of Model-free kinetics, Raman cluster analysis imaging technique, temperature modulated Raman spectroscopy, supplemented with X-ray Photoelectron Spectroscopy analysis, were effective in; 1) distinguishing of carbon phases 2) tracking of oxidation and pyrolytic degradation 3) non-isothermal oxidation kinetic profiling 4) oxidation resistance comparison between SENs 5) oxidation kinetic influences based on chemical, surface area changes and microstructure. Micro–X-ray Computed Tomography provided pore analysis discriminatory values to support the microstructural evaluation of oxidation, whilst at the same time highlighting its potential for macro-crack network analysis related to thermal shock. Laser flash analysis corroborated detection of temperatures linked to microstructural changes of the pore-closure mechanism that was also evaluated by temperature modulated Raman, with results tracking the G-peak shift associated with stress-strain effects. Lastly, the impulse excitation technique was used for evaluating thermal shock resistance of the SENs utilising the Q-factor (dampening) values. When evaluating the preheated SENs, the 3-hour SEN presented a lesser risk factor to thermal shock than the 6-hour, with values of Q-factor: 10.36 and 92.94 respectively. However, the 6-hour showed more resistance to oxidation than the 3-hour when using the graphite cluster phase at conversion ≥ 0.5% and their corresponding temperatures ≥ 650 °C. It appears that lower temperatures showed the virgin to be more resistance to oxidation in relation to the graphite cluster phase only. The virgin sample results of thermal shock were somewhat between the two SENs indicative of a healing process occurring after the diminishing of thermal shock resistance during heating. The Vyazovkin method of activation energy values from the non-isothermal oxidation kinetics profiles for both resin and graphite regions were in the ranged between 150 kJ/mol to 220 kJ/mol.